2017
DOI: 10.1021/acs.analchem.7b02267
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Cell Culture and Drug Testing in a Microfluidic Sidewall-Attached Droplet Array

Abstract: Three-dimensional (3D) cell culture provides an effective way over conventional two-dimensional (2D) monolayer culture to more closely imitate the complex cellular organization, heterogeneity, and interactions as well as tissue microenvironments in vivo. Here we present a novel droplet-based 3D cell culture method by using droplet array attached on the sidewall of a PDMS piece. Such an arrangement not only avoids cells from adhering on the chip surface for achieving 3D cell culture in nanoliter-scale droplets,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 36 publications
(72 reference statements)
3
41
0
Order By: Relevance
“…Meanwhile, Fang's group also prepared the HepG2 spheroids using microfluidic sidewall-attached droplet array, and applied these spheroids to testing of an anticancer drug (doxorubicin). [141] The results also showed that when the doxorubicin concentration was higher than 10 −7 m, the cell survival rate of spheroids was significantly higher than that of 2D cell culture (Figure 7a).…”
Section: Drug Screeningmentioning
confidence: 83%
See 1 more Smart Citation
“…Meanwhile, Fang's group also prepared the HepG2 spheroids using microfluidic sidewall-attached droplet array, and applied these spheroids to testing of an anticancer drug (doxorubicin). [141] The results also showed that when the doxorubicin concentration was higher than 10 −7 m, the cell survival rate of spheroids was significantly higher than that of 2D cell culture (Figure 7a).…”
Section: Drug Screeningmentioning
confidence: 83%
“…Reproduced with permission. [141] Copyright 2017, American Chemical Society. b-i) Schematic illustration of microfluidic device with gradient drug concentrations, and ii) typical images of HCT116 spheroids treated with 5 × 10 −6 m irinotecan at various days.…”
Section: Drug Screeningmentioning
confidence: 99%
“…Several devices have been developed to interrogate drug efficacy in several diseases [ 170 , 171 ]. For the sake of brevity, this section will mainly focus on devices that have been used for cancer treatment including those that have been developed to uncover direct cytotoxic effects [ 172 , 173 , 174 ], effects on cell growth [ 175 ], and pharmacokinetics [ 176 , 177 ]. Devices studying cytotoxic effects are more applicable to both personalized medicine and drug screening, while devices used to examine cell growth and pharmacokinetics provide a greater understanding of drug mechanics inside the cell.…”
Section: Disease Diagnosticsmentioning
confidence: 99%
“…These devices focus on creating more accurate physiological models, increasing the throughput of drug concentrations studies using gradient generators, or allowing for the generation and isolation of 3D spheroids using droplet generators. Zhao et al cultured 3D cell spheroids attached to the sidewall of a PDMS device in a droplet array [ 172 ]. This droplet positioning facilitated drug treatment and cell staining, which was performed by taking advantage of capillary forces.…”
Section: Disease Diagnosticsmentioning
confidence: 99%
“…In particular, in the field of three-dimensional culture models, a diffuse approach includes building spheroids of cells. An example of a microfluidic device based on this method was proposed by Zhao et al [28]. In their work, the authors presented a droplet-based 3D cell culture mode.…”
Section: Introductionmentioning
confidence: 99%